Tribunal do Júri e Soberania Popular - Azevedo, André Mauro Lacerda (2007)
The present work has for object the Jury under the democratic optics, looking for to demonstrate its democratic validation. The purpose of this work was to revisit the institution, in order to bring its importance while instrument of popular participation. The work presents, first, a systematic and chronological approach of the institution of the Jury and its evolution inside of Brazilian constitutional history, objectifying, with this, to approach the narrow entailing of the Jury with the constitutional postulates. After that, the constitutional principles of the Jury had been examined, looking for to establish the popular identity of the institution and its approach with the human rights system of the Brazilian Federal Constitution. More ahead, had been examined the direct participation of the society in the Jury, going deep the questions related with the election of the jurors and the jury nullification on the American Jury. Finally, had been dedicated the study of the current conjuncture of the Brazilian Jury, its problems and the possible solutions, beyond the study of the limitation's mechanisms in the constitutional principle of the popular supremacy and the reform's projects suggested for legislators and jurists. In this way, had been looked elaborate a constitutional construction of the Jury, defending its permanence in the Brasil law system, for being a fundamental guarantee to protect the freedom, moreover for being essential to validate the Democratic State of Right, for to be the materialization of the democratic principle. For opportune, it's necessary to allege that this work had been directed to the constitutional analysis of the Jury, its legitimacy and its democratic vocation, using themselves as ideological north the American Jury System and as philosophical base the social contract theory, understanding the Jury as an instrument of protection of the society front to the state supremacy and its hierarchy structure of the power